Tests and Seismic Response Analysis of Guided-Rail-Type Anti-Tensile Rubber Bearing - Longfei Zhang; Xiang Lan; Kechuan Wu; Wenzheng Yu (Buildings, 2024)
When subjected to seismic activity, tall isolated buildings with a high aspect ratio are susceptible to overturning as a result of the failure of rubber isolation bearings under tension. In order to address this issue, a guided-rail tension device (GR) has been developed to enhance the tensile strength of rubber bearings. Furthermore, a novel guided-rail isolation rubber bearing (GR&RB) has been proposed as a potential solution. Quasi-static tests have been conducted to investigate the mechanical properties of the GR, as well as the GR&LNR600 and LNR600. Additionally, numerical finite element analysis has been employed to study the seismic response of the GR&RB under El Centro seismic action in a high-rise building with an aspect ratio of approximately 4. The experimental results suggest that the inclusion of GRs has a limited effect on the horizontal mechanical attributes of rubber isolation bearings. Nevertheless, it simultaneously enhances their tensile strength, demonstrating a significant augmentation of 4.23 times. Moreover, the mechanical behavior of the GR aligns with the Hook model. The numerical analysis suggests that the utilization of GR&RB can mitigate the tensile stress levels of rubber isolators. Furthermore, it is recommended to augment the elastic tensile stiffness of the GR while reducing the open value to enhance the tensile efficiency, with the potential to attain up to 75% efficiency in tensile performance.